Membangun Karakter Sosial Ekonomi Siswa SD/MI Melalui Pembelajaran Ilmu Pengetahuan Sosial / Building the Social Character of Elementary Education Students Through Learning Social Sciences - Choiru Umatin; Desi Widayanti; Mochamad Nasichin Al Muiz (Al-Mudarris: Journal Of Education, 2023)
This study answers the problems of SD/MI students who lack social character in interacting in their surroundings. This study tries to explain about the efforts of social studies teachers as educators in the formation of social character in SD/MI students. Social character education is an education that is urgent in shaping the child's personality to become a socially good human being with a series of situations. The method / approach used in this paper is the library research approach, while data collection is carried out by examining and exploring a number of journals, documents and books (both electronic and printed) and sources of data and or information. others that are considered relevant to the study. The findings obtained in this study that teachers 'efforts in developing students' social character include exemplary, inculcation or enforcement of discipline, habituation and creating a conducive atmosphere. The teacher also plays the role of instructor in the form of planning and implementing classroom learning. The teacher's role as a motivator and inspiration is manifested in the form of support, example, creativity, appearance, association, ways of communication and social care in the surrounding environment. The teacher's role as a trainer is realized in the form of building character awareness and character education activities in social interaction.